Studi Komparatif Konsepsi Dana Non-halal dan Dana TBDSP dalam Perspektif Politik Ekonomi Islam - Dery Ariswanto (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
This study aims to examine the comparison of the concept of regulation of non-halal funds and TBDSP funds in the perspective of Islamic Political Economy. This research uses qualitative methods with the type of research that is library research. The results of the discussion in this study indicate that the arrangement of non-halal funds was originally only limited to a concept which must then be used for social purposes, but there are no specific rules related to how to obtain or source of these funds, how to manage them, and what are the provisions for their distribution. . Presentation and reporting of non-halal funds have previously been regulated in PSAK 101 and 109. The presence of the DSN fatwa number 123/DSN-MUI/XI/2018 can imply that the concept of non-halal funds should not be recognized as income for Islamic financial institutions. So that the term non-halal funds in Islamic financial institutions is more accurately referred to as TBDSP funds. It is appropriate that maximum supervision is needed in implementing the DSN fatwa regarding TBDSP funds in Islamic financial institutions, so that the management of non-halal funds of Islamic financial institutions can be directed and on target in accordance with existing regulations.